Analysis of Corrosion Breakdown Rate in Low Carbon Steel with Aluminum Coating - Zyahdo Nikri Jofalo; Prantasi Harmi Tjahjanti (Procedia of Engineering and Life Science, 2021)
This study aims to analyze the corrosion penetration rate of low carbon steel with aluminium coating. The method used is the potentiodynamic method to determine the value of the corrosion rate. The corrosion medium used was HCl. The aluminium used is aluminium frame waste powder. The coating process is by dipping low carbon steel pipes into aluminium frame waste that had been liquefied in the Hot Dip Galvanizing (HDG) method of 700oC and immersion time of 45 seconds. The results of this study show that low carbon steel which has been coated with aluminum frame waste powder has a high corrosion rate which is proven to have a corrosion rate of 18,1808 mm/year. So that the corrosion rate is at an unacceptable level.